Comparison of Sharia Banking Performance in Malaysia and Indonesia According to Maqashid Sharia Perspectives - Munir, Misbakhul; Ekawaty, Marlina; Manzilati, Asfi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2024)
Purpose The research objective was to analyze the difference of sharia banking performance in Malaysia and Indonesia through measurement tool of maqashid index of MPEM and PMMS Design/methodology/approach This research used comparative study quantitative method and secondary data with observation period of 2014-2021. Findings Based on the MPEM index of maqashid sharia, this research result referred that Indonesia was superior in the dimension of preserving religion, maintaining wealth, and continuing offspring. Based on PMMS maqashid sharia index, Malaysia was superior to Indonesia in all indicators consisting of educating individuals and upholding justice and welfare. Research limitations/implications The research objective was to analyze the difference of sharia banking performance in Malaysia and Indonesia through measurement tool of maqashid index of MPEM and PMMS period of 2014-2021 Originality/value The countries in Southeast Asia region have applied this Dual Banking System including Indonesia and Malaysia. The use of different system applied in banking field should affect the difference of performance measurement. MPEM and PMMS were taken as alternatives of maqashid sharia-based banking performance measurement which was more proper if it was functioned to measure the performance of sharia banking.